Fungi responsible for seedling emergence problem indifferent soybean cultivars in Tarai region - P.N. THAPLIYAL, UMA SINGH and (Indian Phytopathology, 2002)
Aspergillus flavus, Rhizoctonia solani, Sclerotium rolfsii [Corticium rolfsii], Macrophomina phaseolina and Fusarium pallidoroseum were the most frequently isolated fungi from diseased soyabean seeds/seedlings, collected during June-July 1995-1996 in the Tarai region in Uttar Pradesh, India. All fungi caused significant inhibition in germination, and production of diseased seedlings when tested under laboratory conditions on 5 soyabean cultivars.